Architecture according to pigeons - Tailfeather, Speck Lee (Fictitious character) (Phaidon Press, 2013)
The world's most beautiful buildings are described from a bird's eye view by Speck Lee Tailfeather, a pigeon who is also an aficionado of architecture.